STRENGTHENING ENTREPRENEURSHIP-BASED ISLAMIC EDUCATION IN PONDOK PESANTREN JABAL LUBUK RAYA TAPANULI SELATAN - Siregar, Mustamin (FORUM PAEDAGOGIK, 2024)
Abstract This study aims to examine the strengthening of entrepreneurship-based Islamic education at Jabal Lubuk Raya Islamic Boarding School, Tapanuli Selatan. Entrepreneurship-based education serves as a strategic approach to equip students with practical skills relevant to facing modern economic challenges while preserving Islamic values. The research employed a qualitative approach with data collection techniques including observation, in-depth interviews, and documentation. The findings reveal that Jabal Lubuk Raya Islamic Boarding School has implemented entrepreneurship education through an integrative curriculum combining religious studies with entrepreneurial skills. Key programs include business training, student-run business practices, and project-based learning. Supporting factors include the commitment of pesantren leaders, adequate facilities, and students' enthusiasm for entrepreneurship. However, challenges such as limited funding and gaps between theory and practice remain. This study concludes that strengthening entrepreneurship-based Islamic education at this pesantren significantly contributes to producing independent, innovative, and morally upright students. Keywords: Islamic Education; Entrepreneurship; Islamic Boarding School